“ROLE OF CONSTITUTIONAL HOMOEOPATHIC MEDICINE IN GENERALISED ANXIETY DISORDER” – A CASE STUDY - Dr. Amandeep Kaur; Prof. Dr. Shrimohan Sharma; Dr. Ishita Ganjoo (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Generalised anxiety disorder affects personal and professional life of an individual The World Health Organisation has predicted that the repercussions of the Covid- 19 pandemic on mental health could possibly linger for the coming decades, underlining the robust strategy in managing the mental health disorders.(1) Homoeopathy has a significant role to play in managing this malady.